2020
DOI: 10.3390/ani10061019
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Ensiling on the Nutritional Composition and Fermentation Characteristics of Brown Seaweeds as a Ruminant Feed Ingredient

Abstract: Ensiling could be an effective method to preserve seaweeds for animal feed applications, however, there is limited scientific knowledge in this area. Seaweeds are a promising ruminant feed ingredient, in part due to the content of phenolic compounds, which are receiving considerable interest as alternative antimicrobial agents in feed. The aim of the study was to compare the effect of ensiling on the nutritional composition and fermentation characteristics of two brown seaweed species, Fucus vesiculosus (FV) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
25
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 52 publications
8
25
3
Order By: Relevance
“…Similar to that observed for P. umbilicalis silages, concentrations of other alcohols and esters were negligible (≤0.018 g/kg DM) in S. latissima silages. In agreement with our results, ethanol was the main alcohol in silages of F. vesiculosus , L. digitata and S. latissima silages, and concentrations of other alcohols were minor in previous studies [ 26 , 44 ]. Ethanol content in silages is usually attributed to the activity of epiphytic, salt-tolerant yeast populations [ 47 ].…”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…Similar to that observed for P. umbilicalis silages, concentrations of other alcohols and esters were negligible (≤0.018 g/kg DM) in S. latissima silages. In agreement with our results, ethanol was the main alcohol in silages of F. vesiculosus , L. digitata and S. latissima silages, and concentrations of other alcohols were minor in previous studies [ 26 , 44 ]. Ethanol content in silages is usually attributed to the activity of epiphytic, salt-tolerant yeast populations [ 47 ].…”
Section: Resultssupporting
confidence: 93%
“…In well-preserved silages, lactic acid bacteria are active in degrading water-soluble carbohydrates and the lactate produced causes a decrease in pH that preserves the silage [ 41 ]. The low lactate contents observed in our study are consistent with the greater pH values compared with those reported in previous studies with S. latissima silages previously discussed [ 25 , 26 , 44 ]. Altogether, these results indicate that the activity of lactic acid bacteria in our silages was scarce, and that the good ensilability characteristics of S. latissima reported by other authors were not observed in our study.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations